Functions of Challenging Behaviors and Strategies Utilized to Decrease Challenging Behaviors: Teachers’ and Parents’ Reports of Children with and Without Autism Spectrum Disorder - Javed, Suzzanna (2019)
Challenging behaviors are considered predictors of poor outcomes and children with Autism Spectrum Disorder (ASD) are at increased risk for such behaviors. There is limited research on how the functions of such behaviors and intervention strategies aimed at reducing them may differ by context. Using a researcher-designed survey, this study examined parents’ and teachers’ descriptions of the function of, and strategies for, challenging behaviors among children with and without ASD. A total of 488 respondents completed the survey, including 251 (51.5%) teachers and 237 (48.5%) parents. The participants were recruited in person and via social networking using snowballing and word-of-mouth. The study findings revealed that while both parents and teachers frequently identified avoidance/escape and attention-seeking as functions of challenging behaviors for children with and without ASD, there were some differences in their reports. Most notably, for children with ASD, 28% of parents reported children’s use of challenging behaviors to get attention at home whereas 2% reported this function at school, while 72% of the teachers indicated children’s use of challenging behaviors to seek attention at school and only 10% reported this function at home. The two most common intervention strategies identified by both teachers and parents were reinforcing positive effortful behavior and providing positive attention such as praise and acknowledgement. These finding are critical as they show the differences in the opinions towards the use of challenging behaviors in the home and school settings as reported by parents and teachers and inform future intervention efforts aimed at addressing challenging behaviors in varying contexts.